Individual step characteristics during sprinting in unilateral transtibial amputees - Hobara, H.; Saito, S.; Hashizume, S.; Sakata, H.; Kobayashi, Y. (Journal of Applied Biomechanics, 2018)
To understand the step characteristics during sprinting in lower-extremity amputees using running-specific prosthesis, each athlete should be investigated individually. Theoretically, sprint performance in a 100-m sprint is determined by both step frequency and step length. The aim of the present study was to investigate how step frequency and step length correlate with sprinting performance in elite unilateral transtibial amputees. By using publicly-available Internet broadcasts, the authors analyzed 88 races from 7 unilateral transtibial amputees. For each sprinter`s run, the average step frequency and step length were calculated using the number of steps and official race time. Based on Pearson`s correlation coefficients between step frequency, step length, and official race time for each individual, the authors classified each individual into 3 groups: step-frequency reliant, step-length reliant, and hybrid. It was found that 2, 2, and 3 sprinters were classified into step-frequency reliant, step-length reliant, and hybrid, respectively. These results suggest that the step frequency or step length reliance during a 100-m sprint is an individual occurrence in elite unilateral transtibial amputees using running-specific prosthesis